Effect of Biochar Treatments on Soil Available N and N Uptake by Corn Plants - Shehan, Ruqaya Gabar; Abdulkaream, Mohammed A. (Journal of Science in Medicine and Life, 2025)
Incubation and pot experiments were carried out to study the effect of biochar on available N, N concentration, and N uptake of corn plant grown in two soils. Soils used were clay loam and loamy sand of Basrah province, south of Iraq. The biochar was produced from either corn stover or rice residues. Each biochar was composted with organic residues (alfalfa and poultry) or uncomposted. Three levels (5, 10 and 20 ha -1) as well as control of biochars were tested in the incubation experiment, while 20 ton ha-1 was employed in the pot experiment. Results showed that increased biochar levels significantly increased available N contents in the two soils. N concentration and uptake were increased with 20 ton ha -1 over than control. For biochar source, rice-derived biochar had the higher available N, N concentration and uptake compared with corn- derived biochar in the two soils, with a superiority percents of 8. 94 and 7. 66 % for available N, 5. 81 and 14. 00 % for N concentration, and 35. 29 and 21. 95 and 76. 47 % for N uptake. Composted biochar had the higher available N, N uptake relative to uncomposted biochar. The inceasing percents were 25. 36 and 24. 99 % for available N, 7. 94 and 32. 72% for N concentration and 27. 50 and 93. 37 % for N uptake, at clay and sandy soils, respectively.